A Study on the Factors Influencing the Buying Behaviour of Organic Food Products Amongst Gen Z in Mumbai - Florency Dsouza; Chetan Panchal (International Journal of Sustainability, 2025)
This study explores the key variables that shape the purchasing behavior of Generation Z (Gen Z) consumers in Mumbai with regard to organic products. As awareness about health and sustainability continues to grow, understanding the preferences of this consumer group has become increasingly important. The research is based on a structured quantitative survey conducted among 100 Gen Z consumers residing in Mumbai. The responses reveal that several factors, including price, social influence, health consciousness, and environmental concerns, significantly affect the intention of Gen Z individuals to purchase organic goods The findings suggest that affordability remains one of the strongest determinants, as young consumers are often price-sensitive. At the same time, peer groups, family opinions, and social media exposure play a crucial role in shaping attitudes toward organic products. Health consciousness is another strong motivator, with many respondents associating organic goods with reduced chemicals, better nutrition, and long-term wellness. Environmental concerns also emerge as a vital driver, as Gen Z tends to value sustainable practices and eco-friendly lifestyles. Interestingly, the study highlights that Gen Z consumers are more likely to buy organic products when they perceive them as natural, healthy, and environmentally safe. These perceptions enhance trust and willingness to pay a premium. For marketers, the findings underline the importance of promoting transparency, clear labeling, and sustainability-focused branding. For policymakers, the results emphasize the need for supportive measures such as subsidies, awareness campaigns, and certification standards to increase accessibility. Overall, the study provides practical insights for promoting organic products among urban Gen Z consumers in India.
Keywords: Gen Z; India; buying behaviour; mumbai; organic products